Pengaruh Pengetahuan Perpajakan, Sosialisasi Perpajakan, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Dalam Membayar PBB - Ranti Dela Arrasi (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
Land and Building Tax is an important income for each region, therefore each local government has its own way to optimize income from the Land and Building Tax sector. This study aims to analyze the effect of tax knowledge, tax socialization and tax sanctions on taxpayer compliance in paying land and building taxes in the city of Pekanbaru, either partially or simultaneously. This research was conducted on individual taxpayers registered at the Regional Revenue Agency (BAPENDA) Pekanbaru City. This research is a descriptive research that uses a quantitative approach. The sample method is Accidental Samplin with a total of 100 taxpayers. The data in this study are primary data using a questionnaire that has been reviewed for validity and reliability. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that the variables of knowledge, socialization and tax sanctions have a positive and significant effect on taxpayer compliance in paying PBB. Keywords: Tax Knowledge, Tax Socialization, Tax Sanctions, Taxpayer Compliance.